Adapting to Mediterranean island environments: prehistoric human interaction with plants and animals at Piano dei Cardoni (Ustica) and Mursia (Pantelleria) - Speciale, Claudia; Carra, Marialetizia; Fiori, Fabio; Prillo, Vito Giuseppe; Allué, Ethel; Cattani, Maurizio (Frontiers in Environmental Archaeology, 2025)
This study investigates prehistoric human adaptation to small Mediterranean island environments through the archaeobotanical and zooarchaeological analysis of two key sites: Piano dei Cardoni (Ustica, Neolithic) and Mursia (Pantelleria, Bronze Age). Both volcanic islands, differing in size, landscape features, and chronology of occupation, offer an ideal framework to explore how early human communities managed limited insular resources, navigated ecological constraints, and established sustainable subsistence systems. On Ustica, permanent settlement during the Middle Neolithic (c. 4800–4300 BCE) is reflected in a diversified exploitation of local vegetation and faunal resources. Archaeobotanical evidence suggests the co-occurrence of plant species linked to natural and anthropogenic habitats, including barley, fig, olive, and lentisk, possibly indicating deliberate introduction of tree crops for long-term occupation. Shrubland and woodland species were utilized without evident overexploitation, and faunal remains show a subsistence economy based on ovicaprines, complemented by wild birds and marine resources. The absence of large mammals and the reduced size of domesticates highlight adaptive strategies in a resource-limited setting. In contrast, Bronze Age Pantelleria (c. 1800–1500 BCE) shows a more structured subsistence model within a larger, ecologically more complex island. The Mursia settlement reveals a shift in plant use across its occupational phases, from cereal- and pulse-based agriculture to increased exploitation of wild plants like purslane and crop trees like fig. Wood charcoal indicates probably a technological selection of plant species, with a prevalence of pine, juniper, and heather. Zooarchaeological data reveals a dominant use of ovicaprines, marine fish, and mollusks, with a possible reorganization of livestock strategies over time. Comparative analysis reveals both continuity and divergence in insular adaptation. While both sites demonstrate human resilience through mixed subsistence strategies combining agriculture, foraging, and marine exploitation, local environmental and cultural factors drove distinct responses. The findings underscore the importance of interdisciplinary approaches in understanding human-environment interactions and the role of islands as dynamic laboratories of ecological and cultural experimentation during prehistory.